211k views
23 votes
Question 5 of 10

What is the first step in solving a quadratic equation of the form given below?
(ax+ b)² = c
O A. Divide both sides by c
OB. Factor out a common factor
OC. Use the zero product rule
OD. Take the square root of both sides

User Cbeuker
by
4.3k points

2 Answers

9 votes

Answer:

D

Explanation:

(ax + b)² = c

step 1 : take square root of both sides

ax + b = ±
√(c)

step 2 : subtract b from both sides

ax = - b ±
√(c)

step 3 : divide both sides by a

x = -
(b)/(a) ±
(√(c) )/(a)

User Loler
by
5.8k points
8 votes

Answer:

D. Take the square root of both sides

Explanation:

Given quadratic equation:


(ax+b)^2=c

To solve, square root both sides:


\implies √((ax+b)^2)=√(c)


\textsf{Apply radical rule} \quad √(n^2)=n, \quad \textsf{assuming }n \geq 0:


\implies ax+b=\pm√(c)

Subtract b from both sides:


\implies ax=-b\pm√(c)

Divide both sides by a:


\implies x=(-b\pm√(c))/(a), \quad a\\eq 0

User Ian Sudbery
by
5.0k points